Hummingbirds of Hollywood [videorecording (DVD)] - Masear, Teresa E., 1959- (PBS, 2025)
Amid the glamour of Hollywood, Terry Masear finds herself on a transformative journey as she nurtures wounded hummingbirds, unraveling a visually captivating and magical tale of love, fragility, and healing. Meet Cactus, Jimmy, Wasabi, Alexa, and Mikhail, Masear's diminutive patients, as we celebrate their small victories while lamenting their tiny tragedies. The compassion and empathy that Masear shows her Lilliputian charges serve as a lesson to us all--the delicate beauty in profound acts of kindness.